2016
DOI: 10.12933/therya-16-335
|View full text |Cite
|
Sign up to set email alerts
|

Spatial ecology of a herd of white-lipped peccaries (Tayassu pecari) in Belize using GPS telemetry: challenges and preliminary results

Abstract: The Maya Mountains are a heavily forested mountain range in Belize and Guatemala supporting high levels of biodiversity. Due to environmental degradation around the range, it is in danger of becoming isolated from the largest contiguous forest in Central America. Forest connectivity in the area is vital for white-lipped peccaries. These social ungulates roam in herds of up to 300 individuals and need large forested areas to sustain populations. The species has not previously been studied in Belize and its dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
1
3
0
1
Order By: Relevance
“…( 2019 ) estimated an 100% MCP of only ~8 km 2 for Darién National Park in Panamá, but these authors monitored WLPs using GPS collars and reported home ranges of 25–59 km 2 using AKDE. These estimates are similar to those in other tropical and subtropical forest studies using the same approach, such as 49 (32–69) km 2 and 34 (25–45) km 2 for a male and a female in French Guiana, respectively (Richard‐Hansen et al., 2019 ); 55 (34–81) km 2 in Belize (Hofman et al., 2016 ), and our average estimates of 57.7 km 2 from the five individuals we tracked.…”
Section: Discussionsupporting
confidence: 87%
“…( 2019 ) estimated an 100% MCP of only ~8 km 2 for Darién National Park in Panamá, but these authors monitored WLPs using GPS collars and reported home ranges of 25–59 km 2 using AKDE. These estimates are similar to those in other tropical and subtropical forest studies using the same approach, such as 49 (32–69) km 2 and 34 (25–45) km 2 for a male and a female in French Guiana, respectively (Richard‐Hansen et al., 2019 ); 55 (34–81) km 2 in Belize (Hofman et al., 2016 ), and our average estimates of 57.7 km 2 from the five individuals we tracked.…”
Section: Discussionsupporting
confidence: 87%
“…This nonrandom preference for habitats in T. pecari underscores the importance of a diverse array of forest types and their associated fruiting species (Keuroghlian et al 2009). Tayassu pecari avoided agricultural environments (Hofman et al 2016), secondary forests, and forest plantations (Vindolin et al 2009), focusing on forested areas, including riparian zones, in which the availability of water shapes its patterns of habitat use significantly (Fragoso 1999;Keuroghlian and Eaton 2008;Reyna-Hurtado et al 2009) (Romero et al 2013), which may reflect its adaptability to a wider range of conditions in comparison with other peccary species (Altrichter and Boaglio 2004).…”
Section: Discussionmentioning
confidence: 92%
“…However, collared peccary (solitary individuals or herds reaching ~15 individuals) was recorded only at two camera-trap stations (S1 and S2), which are near to reserve buildings and the border with a cattle ranch, while white-lipped peccary (always in herds reaching ~80 individuals) has been recorded at four camera-trap stations (S4, S5, S6, and S8) in isolated areas under low disturbance. White-lipped peccaries are described to have a seasonally varied home range much larger than the stable collared peccaries home range (Peres, 1996;Fragoso, 1998;Keuroghlian et al, 2004;Hofman et al, 2016), which can explain the slightly higher number of white-lipped peccaries records. Although studies have reported niche overlap between these species, collared peccaries forage at a different time period to avoid competition with white-lipped peccaries (Desbiez et al, 2009;Galetti et al, 2015).…”
Section: Resultsmentioning
confidence: 97%